2020
DOI: 10.1111/ggi.13981
|View full text |Cite
|
Sign up to set email alerts
|

Changes in trust and trait anxiety: The mediating role of changes in self‐rated health among older adults in Taiwan

Abstract: Aim This study examined whether changes in generalized trust and bonding trust are related to changes in trait anxiety, and whether changes in self‐rated health mediate the relationship between changes in two types of trust and trait anxiety among older Taiwanese adults. Methods A hierarchical regression model and a mediation model were separately used to analyze two‐wave panel data on 763 older adults from the Panel Study of Family Dynamics in Taiwan. Results Our findings show that changes in bonding trust (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Empirical studies have shown that social trust at the individual level is strongly associated with anxiety ( 57 ). Social trust is believed to relieve individual emotional responses to anxiety by increasing perceived or actual social support ( 58 ). In China, especially for elderly adults, social trust is mainly reflected in the family or a narrow circle of interpersonal relationships, such as trust in family members, neighbors, and friends ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies have shown that social trust at the individual level is strongly associated with anxiety ( 57 ). Social trust is believed to relieve individual emotional responses to anxiety by increasing perceived or actual social support ( 58 ). In China, especially for elderly adults, social trust is mainly reflected in the family or a narrow circle of interpersonal relationships, such as trust in family members, neighbors, and friends ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the accumulation of individual anxiety may trigger a series of social anxiety symptoms ( Ng-Cordell et al, 2018 ). It was noted that trust is beneficial to reducing anxiety ( Flugelman et al, 2020 ; Jhang, 2020 ); in other words, anxiety may add distrust regarding relevant departments. A previous study showed that a lower level of anxiety was associated with trust in the healthcare system ( AlRuthia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive searches for health-related information are anxietyprovoking (2), and accumulation of individual anxiety may trigger a series of social anxiety symptom (3). It was noted that trust is bene cial for reducing anxiety (4,5), in other words, anxiety may add distrust of relevant departments. What's more, at high level, anxiety may contribute to increased possibility of affected by a public health emergency(6) and in uences of an pandemic may in turn to increase the level of anxiety.…”
Section: Introductionmentioning
confidence: 99%